PROTOTYPE WARNING SISTEM AKSES PINTU RUMAH BERBASIS MICROCONTROLLER ESP 8266 DAN ESP 32 CAM MENGGUNAKAN SENSOR MAGNETIC SWITCH DENGAN NOTIFIKASI TELEGRAM - sholahuddin, sholeh; Bagus Wahyu Pandhito; Yose Eduar Muda (Jurnal Teknorama (Informatika dan Teknologi El Rahma), 2025)
This research aims to produce a prototype warning home door access system based on the internet of things using 1 nodemcu the brain of the system, buzer as a sound conductor, magnetic reed switch and 1 esp 32 cam as the brain of the camera system. The system development method uses Prototype and the system development model also uses prototype. System testing is done through black-box testing. Data collection techniques in this study using observation and literature study. The results showed that the prototype warning system for home door access based on the internet of things (iot) using the esp8266 microcontroller and esp 32 cam with telegram notification is expected to be able to provide early warning in real time when the door of the house is entered by the thief.